Governance systems and CEO tenure on ESG disclosure scores in the banking industry - Teja, Adrian (University of Merdeka Malang, 2023)
The study aims to understand the effect of governance systems, i.e., Anglo-Saxon and Continental, and CEO tenure on ESG (Environmental, Social, and Governance) and each pillar, i.e., E, S, and G disclosure scores. The sample is banking stock in ASEAN (Association of Southeast Asian Nations) countries, such as Indonesia, Malaysia, Thailand, and the Philippines, for 2015-2021. The data is analyzed using panel data regression. The findings show that Continental governance systems experience faster improvement in ESG and E disclosure scores than Anglo-Saxon governance systems but failed to catching-up on G disclosure scores; CEO with longer tenure has more commitment to ESG and E disclosure scores; and the CEO, regardless of their tenure, already have the commitment for S and G disclosure scores. DOI: 10.26905/jkdp.v27i3.11383